Studies on electrical conductance and activation parameters of parchment supported lead molybdate model membrane - Mohd Ayub Ansari,; Dileep Kumar Singh,; Haider Iqbal,; Manoj Kumar, (Vietnam Journal of Science and Technology, 2025)
The ion-interaction approach was used to develop a lead molybdate parchment supported membrane. FT-IR, XRD,  TGA, SEM, TEM, and EDX investigations were used to determine the physicochemical parameters. At temperatures ranging from 10 to 50°C, the membrane conductivity in contact with different alkali metal ions was investigated.. The electrical conductivity of the membrane was discovered to increase with temperature. The value of membrane conductance for metals follows the cation sequence: K+> Na+> Li+. Using the proper procedure, the thermodynamic activation parameters, such as Ea, ΔHo, ΔGo, and ΔSo were calculated using the appropriate method. The ΔSo values were found to be negative, suggesting that diffusion occurs in the membrane phase with partial immobilisation